Potenciales relacionados con eventos en denominacion de figuras en la Enfermedad de Alzheimer - Quiroz Gaviria, Yakeel Tatiana; Bobbes Leon, Maria Antonieta; Lopera Restrepo, Francisco Javier (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
By recording Event-Related Potentials· 1he aim of this research .was to determine whether there are different brain systems involved in the denomination process. To understand the semantic deterioration observed in patients with Alzheimer’s disease (AD), we carried out three experiments that tested the denomination process at different stages: I) Spontaneous denomination, 2) Semantic clue denomination and 3) Phonologic clue denomination. Indeed, we found different activation centers for each of the stages studied and we observed a specific degree of alteration of these systems in AD patients. We therefore conclude that throughout the progress of cognitive impairment in AD, the semantic system is affected before the phonologic system.